(untitled) (The Peerian Journal, 2022)
Origin and history of field spectacles. Findings reflecting traditions of Ferghana Valley, Samarkand and other regions. The national games of the Timurid and Baburi periods were theoretically analyzed on the basis of the scientists’ researches about the artists.